On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Conceptualiser l’oppression épistémique - Dotson, Kristie (Recherches féministes, 2018)
L’oppression épistémique désigne une exclusion épistémique persistante qui empêche ou limite la contribution d’une personne à la production des savoirs. On hésite à parler d’« oppression épistémique », et cela tient peut-être à la prémisse voulant que les formes épistémiques de l’oppression se ramènent en général à ses formes politiques et sociales. L’auteure convient que de nombreuses formes d’exclusion qui compromettent la capacité d’une personne à contribuer à la production des savoirs peuvent être ramenées à des formes d’oppression politique et sociale, mais il existe néanmoins des formes distinctes et irréductibles d’oppression épistémique. Elle soutient ainsi que la différence fondamentale entre les formes réductibles et irréductibles d’oppression épistémique réside dans le type de résistance à laquelle on fait face dans chaque cas, c’est-à-dire le pouvoir épistémique ou les caractéristiques des systèmes épistémologiques. La distinction entre les formes réductibles et irréductibles d’oppression épistémique permet de mieux comprendre les enjeux que soulève l’emploi de cette expression et la pertinence d’y recourir.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; invisibilisation; phi4336; philosophie; premier cycle; production des savoirs; pédagogie; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

“Me Too”: Epistemic Injustice and the Struggle for Recognition - Jackson, Debra L. (Feminist Philosophy Quarterly, 2018)
Congdon (2017), Giladi (2018), and McConkey (2004) challenge feminist epistemologists and recognition theorists to come together to analyze epistemic injustice. I take up this challenge by highlighting the failure of recognition in cases of testimonial and hermeneutical injustice experienced by victims of sexual harassment and sexual assault. I offer the #MeToo movement as a case study to demonstrate how the process of mutual recognition makes visible and helps overcome the epistemic injustice suffered by victims of sexual harassment and sexual assault. I argue that in declaring “me too,” the epistemic subject emerges in the context of a polyphonic symphony of victims claiming their status as agents who are able to make sense of their own social experiences and able to convey their knowledge to others.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; harcèlement sexuel; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; philosophie féministe; périodes historiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éthique

The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences